Mejoramiento genético. Mejjoramiento de caracteres. Patología - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
During 1985 work in bean pathology at CIAT was concentrated on angular leaf spot, root rot pathogens, and halo blight. The main activities regarding these 3 diseases was the identification of new and better sources of disease resistance. Work was also carried out with rust, Ascochyta, web blight, and common bacterial blight diseases. As in previous years, the principal activities were related to evaluation of bean germplasm for their reaction to disease pathogens. Both segregating and advanced uniform bean nurseries as well as international bean disease nurseries were evaluated mainly under field conditions in several locations. (CIAT)